How to Perform Videos in Dermatologic Surgery? A Simple and Inexpensive Recording Technique - Bruno Duarte; João Goulão (Sociedade Portuguesa de Dermatologia e Venereologia, 2019)
Video recording surgical procedures is one of the most valuable tools for teaching and self-assessment in Dermatologic Surgery. A number of recording systems have been described in the literature. Nevertheless, they're usually expensive (~500€) and time-consuming to prepare, the latter being a major disadvantage for a busy surgical speciality such as Dermatology. The authors describe a simple and inexpensive technique for surgical video capture in Dermatologic Surgery. For this setup, the surgeon needs only a smartphone with a camera (which is nowadays ubiquitous), a bike phone holder (10€ to 30€), an adjustable intravenous pole and, optionally, a powerbank. With the patient in position for the surgical intervention (seated or lying on his back on the surgical table, depending on the procedure), the bike phone holder should be attached to the vertically adjustable intravenous pole. The smartphone must be then set on the bike phone holder, with its "recording mode" already started. Optionally, a powerbank can also be attached to the intravenous pole to provide extra charge for longer procedures. The height of the intravenous pole, as well as its position and distance to the surgical table, should be adjusted accordingly before the intervention, in order to provide the best recording definition. The authors describe a simple, easy to setup, inexpensive system to record videos in Dermatologic Surgery.